IgA vasculitis in Henoch-Schönleinpurpura - Yeganeh, Mehrnoush Hassas; Shiari, Reza; Rahmani, Khosro (Journal of Pediatric Nephrology, 2016)
Henoch-Schönleinpurpura (HSP), also termed IgA vasculitis(IgAV), is a systemic vasculitis with anoutstanding cutaneous involvement.Henoch-Schönleinpurpura (HSP) is a small-vessel vasculitisfeatured by palpable purpura on the lower extremities and IgA-dominant immune complex deposition within the wall and lumen of dermal vessels in the lesions. This disorder is associated with joint, gastrointestinal and renal involvement, although the level and severity of involvement is variable.The histologic findings in the kidney are identical to those in IgAnephropathy. Additionally,high circulating levels of galactose-deficient IgA1 are found in patients with both IgAnephropathy and HSP (IgAV). Both of these two findingsadvocate that the two disorders may have a common pathogenesis.